Analisis Pengaruh Rasio Keuangan Terhadap Kinerja Bank Umum di Indonesia - Rebecca Stephani; Moh. Adenan; Anifatul Hanim (UPT Penerbitan Universitas Jember, 2017)
Banks is an institution, which has mainly activity is fund deposit from people then credit it for them in generating income. The business is a kind service provider from and into people so it needs public trust. Profitability is one of indicator appropriate to measure the bank performance. Return on Assets (ROA) is measure ability of the bank's management in benefits through total assets owned. The greater the ROA shows the better financial performance due to the greater profit. The purpose of this research is to prove the effect of Operating Expenses and Operating Income Ratio, Net Interest Margin (NIM), Non-Performing Loan (NPL) and Loan to Deposit Ratio (LDR) on bank performance measured by Return On Asset (ROA). The study focused on descriptive quantitative analyses using Ordinary Last Square method (OLS). The result of the research showed that partially NPL and NIM had positive and not significant influence on ROA, but LDR and BOPO had negative and significant influence on ROA. Keywords: financial ratio, and bank performance.